2014
DOI: 10.1002/cssc.201402100
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous Flow Strategy for the Coupled Transfer Hydrogenation and Etherification of 5‐(Hydroxymethyl)furfural using Lewis Acid Zeolites

Abstract: Hf-, Zr- and Sn-Beta zeolites effectively catalyze the coupled transfer hydrogenation and etherification of 5-(hydroxymethyl)furfural with primary and secondary alcohols into 2,5-bis(alkoxymethyl)furans, thus making it possible to generate renewable fuel additives without the use of external hydrogen sources or precious metals. Continuous flow experiments reveal nonuniform changes in the relative deactivation rates of the transfer hydrogenation and etherification reactions, which impact the observed product di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
182
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 185 publications
(191 citation statements)
references
References 88 publications
6
182
2
Order By: Relevance
“…They found that increasing the hydrophobicity of the material via silylation allowed the material to retain 50% of its activity even with 10 wt% water in the feed. For the coupled MPV reduction and etherification of HMF in ethanol, the addition of 0.2 wt% water decreases the etherification activity of Hf-Beta by 50%, whereas in 2-butanol, the same amount of water has negligible effect on the activity (25).…”
Section: Reversible Deactivationmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that increasing the hydrophobicity of the material via silylation allowed the material to retain 50% of its activity even with 10 wt% water in the feed. For the coupled MPV reduction and etherification of HMF in ethanol, the addition of 0.2 wt% water decreases the etherification activity of Hf-Beta by 50%, whereas in 2-butanol, the same amount of water has negligible effect on the activity (25).…”
Section: Reversible Deactivationmentioning
confidence: 99%
“…For example, the MPV reduction of cyclohexanone has the highest rates over Sn-Beta by a factor of 4.5, but if the reactant is switched to benzaldehyde, Zr-Beta has the highest rates (10). Similarly, for the combined MPV reduction and etherification of 5-(hydroxymethyl)furfural (HMF) to 2,5-bis(ethoxymethyl)furan (25) and the cross-aldol condensation of aromatic aldehydes and acetone (26), both featuring a dual-binding transition state, we observe higher reactivity over Hf-and Zr-Beta and lower reactivity over Sn-Beta. Table 1 shows that Ti-zeolites are most active for epoxidations; Sn-zeolites are most active for BV oxidation and intramolecular carbon and hydride shifts; and Zr-and Hf-zeolites are equally or more active for intermolecular hydride shifts, etherifications, and aldol condensations.…”
Section: Correlating Heteroatom Identity and Catalytic Activitymentioning
confidence: 99%
See 3 more Smart Citations